Analysis and Matching Calculation of Hydraulic Drive System of Tractor. (November 2020) - Jing, Zhou
Abstract: Firstly, the matching principle of engine and hydraulic torque converter working together is introduced. Then, the mathematical model of matching input and output between tractor engine and hydraulic torque converter is established. The least square fitting method is adopted to fit the characteristic curves of tractor engine and hydraulic torque converter. The vehicle performance is evaluated by calculating the traction characteristics of the vehicle, which not only reduces the workload, but also improves the calculation accuracy